2020
DOI: 10.1007/s40858-019-00326-8
|View full text |Cite
|
Sign up to set email alerts
|

Hosts of asexual morph of Erysiphe quercicola from Thailand

Abstract: Between 2002 and 2017, asexual morphs of powdery mildews (Erysiphales) were collected in Thailand from the following hosts: Cassia fistula, Castanopsis argyrophylla, Durio zibethinus, Jatropha curcas, Kydia calycina, Hevea brasiliensis, Hodgsonia macrocarpa, Mallotus philippinensis, Mimosa pudica, Nephelium lappaceum, Tamarindus indica and Ziziphus jujuba. Combined molecular and morphological analyses revealed that all these specimens belong to Erysiphe quercicola. Sequences retrieved from these powdery mildew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The sequences of the PMs used in this study are listed in Table 1 [9,11,19,[24][25][26]29,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. To determine the phylogenetic relationships using ITS and concatenated sequences of ITS and TUB2, the sequences were aligned using the MAFFT v.7 online version (https://mafft.cbrc.…”
Section: Molecular Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…The sequences of the PMs used in this study are listed in Table 1 [9,11,19,[24][25][26]29,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. To determine the phylogenetic relationships using ITS and concatenated sequences of ITS and TUB2, the sequences were aligned using the MAFFT v.7 online version (https://mafft.cbrc.…”
Section: Molecular Phylogenymentioning
confidence: 99%
“…In the present study, the occurrence periods of the PMs in the winter and spring imply they prefer mild weather instead of excessively high temperature (up to 35 • C) in summer, and it is suggested that the PMs in the subtropical regions may stay in a quiescent state in their hosts during hot summers. However, chasmothecia are rarely formed in subtropical and tropical environments [23,47,77,94]. Thus, the reservoirs of the PMs on all their possible hosts as mycelia or other structures are crucial for their survival and for the infection in the next season.…”
Section: Perennation Of Powdery Mildews In the Subtropics And The Imp...mentioning
confidence: 99%
“…Depending on the specimen and likely also the environment, host plant, and the investigator, remarkable morphological differences were found in the anamorph stages, e.g., lengths of foot cells of conidiophores and conidia and numbers of conidiophores per hyphal mother cell. Teleomorph development in Erysiphales is generally rare in low altitudes of tropical and subtropical regions (Meeboon and Takamatsu 2020). Kuo et al (1991), however, found ascomata of P. xanthii (as S. fusca) in the winter season in central Taiwan.…”
Section: Podosphaera Xanthii In Taiwanmentioning
confidence: 99%
“…For obtaining DNA from powdery mildews, careful selection of clean, fresh specimens is necessary, since powdery mildews cannot be cultivated in vitro, are often contaminated by other microscopic fungi and DNA deteriorates quickly during drying specimens. In Erysiphales, the ITS is the single available barcode for species identification particularly through the accomplishments of Takamatsu (Takamatsu et al 2015a , b ; Meeboon and Takamatus 2016 , 2017a , b , 2020 ). Five species of powdery mildews were identified here based primarily on ITS sequence data.…”
Section: Discussionmentioning
confidence: 99%
“…Under tropical/subtropical conditions, however, instead of rarely formed ascomata, asexual structures such as mycelial appressoria, conidiophores and conidia of the anamorph stage provide the single morphological features which are less diagnostic for morphological species identification (Piepenbring et al 2011 ). Under such conditions, sequences of the internal transcribed spacer (ITS) of the ribosomal RNA genes have become an important tool for species identification (Takamatsu et al 2015a , b , Meeboon and Takamatsu 2016 , 2017a , b , 2020 ; Khodaparast et al 2019 ). Identification and documentation of Erysiphales in Taiwan started over one hundred years ago, followed by occasional records of few other mycologists and plant pathologists as compiled by Kuo ( 1998 ) and subsequent publications (Kirschner and Chen 2008 ; Kirschner and Liu 2014 ; Chen and Kirschner 2018 ; Yeh et al 2018 ; Kirschner et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%